Pengaruh Etika Kerja, Iklim Organisasi dan Keadilan Organisasi Terhadap Kinerja Karyawan Pada Rumah Sakit Ibu dan Anak (RSIA) Puri Bunda Denpasar - Herlambang, Putu Gede Denny; Mastrini , Ni Luh Putu Sri; Sukanti, Ni Ketut (Universitas Pendidikan Ganesha, 2024)
There are several factors that can affect employee performance, including work ethics, organizational climate and organizational justice. The purpose of this research was to determine the influence of work ethics, organizational climate and organizational justice partially or simultaneously on employee performance at the Rumah Sakit Ibu dan Anak (RSIA) Puri Bunda Denpasar. The number of samples in this research were 79 employees who were taken by the slovin method and the sampling technique was simple random sampling. Data were analyzed using classical assumption test, multiple linear regression analysis, analysis of determination, F-test and t-test. The results showed that partially or simultaneously work ethics, organizational climate and organizational justice had a positive and significant influence on employee performance at the Rumah Sakit Ibu dan Anak (RSIA) Puri Bunda Denpasar.